Balancing Environment and Development Costs, Revenues, and Benefits of the Western Riverside County Multiple Species Habitat Conservation Plan - Dixon, Lloyd (RAND Corporation, 2008)
The Western Riverside County Multiple Species Habitat Conservation Planmitigates development effects on 146 plant and animal species byestablishing a 500,000-acre conservation reserve. This monograph examinesland-acquisition strategies and costs, revenue adequacy and potential newfunding sources, the plan's habitat-conservation goals, and whether the planhas streamlined transportation and development permitting processes.